Engendering agricultural research - Meinzen-Dick, Ruth S.; Quisumbing, Agnes R.; Behrman, Julia A.; Biermayr-Jenzano, Patricia; Wilde, Vicki; Noordeloos, Marco; Ragasa, Catherine; Beintema, Nienke M. (International Food Policy Research Institute, 2010)
This paper makes a case for gender equity in the agricultural R&D system. It reviews the evidence on exactly why it is important to pay attention to gender issues in agriculture and why it is necessary to recognize women's distinct food-security roles throughout the entire value chain-for both food and nonfood crops, marketed and nonmarketed commodities. The authors examine whether women are factored into the work of research institutions, and whether research institutions effectively focus on women's needs. In short, are these institutions conducting research by and for women? The paper's conceptual framework demonstrates the need to integrate gender into setting agricultural priorities; conducting the research itself; designing, implementing, and adopting extension services; and evaluating their impacts. It concludes with recommendations regarding how to make these suggested changes.